Home Environment and Larva Indices: A Cross-Sectional Study in the Indonesian Transition to Endemic COVID-19 - Tri Wahyuni Sukesi; Sulistyawati Sulistyawati; Herman Yuliansyah; Surahma Asti Mulasari; Arfiani Nur Khusna; Fatwa Tentama; Bambang Sudarsono; Fanani Arif Ghozali (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
This study aimed to assess the association between home environment and larval indices during the COVID-19 pandemic transition. A cross-sectional design was carried out in this study. The population was the houses in two villages of Gamping Sub-District, Sleman, Yogyakarta Province. The sample was calculated by considering the confidence interval value of 95%, the margin error of 5%, and the distribution response of 50%. Accordingly, the minimum sample size was 207 households. The chi-square test was used to analyze the data. The home environment was associated with the value of the container index (CI), indicated by a significant difference p-value of 0.008 with a prevalence ratio of 3.630, which means an unhealthy house will increase the value of the container index by 3.630 times greater. Sanitation of the home environment showed a significant relationship with the value of the container index (CI) with a p-value of 0.019 and a prevalence ratio of 2.625, which means that poor sanitation conditions will increase the value of the container index by 2.625 times. The health of the home environment is associated with the mosquito larvae index.Â